(untitled) (Research, Society and Development, 2022)
The use of hydrological models allows to understand, evaluate and anticipate events of natural or man-made origin in a simpler and more economical way for the quantity and quality of resources in a hydrographic basin. The present work aims to perform a hydrological modeling in the hydrographic basin in the semiarid, using the SWAT model, to verify the influence of the use and exploitation of water production on the land. For this, the SWAT hydrological model (Soil Water Assessment Tool) was used. A study area located in the Jacaré Curitiba Basin, in Poço Redondo-SE, a semi-arid region of the state, inserted in the Caatinga biome and in the lower São Francisco. The adopted methodology was used for bibliographic survey, field work, hydrological monitoring, chemical and physical medicine of soil and soil, survey of land use and exploration, calibration and validation of hydrological model. The SWAT model successfully simulated or hydrographed the flow for the period from Nov/2015 to Jul/2018, duly calibrated and validated. As simulations of different land use scenarios, the greatest production of water in agricultural areas stands out, which can cause greater generation of sediments. The calibrated and validated SWAT model means a possibility for future studies in non-semiarid watersheds and then contributes to studies on water and soil management.